Rumble in the jungle - Andreae, Giles, 1966- (Wilton, Conn. : Tiger Tales, 2001)
A poetic exploration of the hippos, leopards, chimpanzees, and other animals found in the jungle.
NP
Accelerated Reader AR
Keywords: Jungle animals -- Juvenile poetry; Children's poetry, English; Jungle animals -- Poetry; English poetry